ANALISIS IMPLEMENTASI PERATURAN DAERAH KABUPATEN SERANG NOMOR 3 TAHUN 2019 TENTANG PENGELOLAAN PERSAMPAHAN - Azzaria, Talitha Anggun; Bangsawan, Try Adhi; Saepudin, Eli Apud (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
Waste management is an environmental challenge that requires special attention, especially in traditional markets that generate significant volumes of waste. In an effort to create a clean and healthy environment, the Serang Regency Government has issued Regional Regulation No. 3 of 2019 concerning Waste Management. This study aims to assess the implementation of this regulation at Cikande Market, identify emerging obstacles, and evaluate the roles of the local government, market managers, and the community in supporting effective waste management. This study used a qualitative method with a descriptive approach, where data were collected through observation, interviews, and documentation. Data analysis was conducted with reference to the Van Meter and Van Horn policy implementation model, which includes policy standards and objectives, resource availability, inter-organizational communication, implementer characteristics, socio-economic and political conditions, and implementer dispositions. The results show that the implementation of Regional Regulation No. 3 of 2019 at Cikande Market is not optimal. Contributing factors include limited waste management facilities and infrastructure, a lack of transportation vehicles, weak coordination between relevant agencies, and low public awareness and participation. The roles of the local government and market managers have been implemented, but have not been optimally integrated. Meanwhile, community participation is largely limited to paying fees, without accompanying compliance with proper waste management. Therefore, improved coordination, additional facilities, and strengthened outreach and community participation are needed to ensure more effective and sustainable waste management at Cikande Market.